2017
DOI: 10.1002/2016tc004285
|View full text |Cite
|
Sign up to set email alerts
|

Birth, life, and demise of the Andean–syn‐collisional Gissar arc: Late Paleozoic tectono‐magmatic‐metamorphic evolution of the southwestern Tian Shan, Tajikistan

Abstract: The amalgamation of the Central Asian Orogenic Belt in the southwestern Tian Shan in Tajikistan is represented by tectono‐magmatic‐metamorphic processes that accompanied late Paleozoic ocean closure and collision between the Karakum‐Tarim and Kazakh‐Kyrgyz terranes. Integrated U‐Pb geochronology, thermobarometry, pseudosection modeling, and Hf geochemistry constrain the timing and petro‐tectonic nature of these processes. The Gissar batholith and the Garm massif represent an eastward, along‐strike increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 125 publications
(366 reference statements)
2
21
1
Order By: Relevance
“…Therefore, these data reveal that the final suturing of the southwestern CAOB was achieved by northward subduction of the South Tianshan Ocean and subsequent collision of the CTB and the Karakum-Tarim cratons at~320 Ma. Notably, recent studies suggest that a trench-arc-back-arc basin system developed in the northern Karakum during Carboniferous times Worthington et al, 2017), which differs from the here suggested tectonic evolution that favors a transition of the northern Tarim Craton from a trench-arc-back-arc system to a passive margin at~390-380 Ma.…”
Section: 1029/2018jb015689contrasting
confidence: 94%
“…Therefore, these data reveal that the final suturing of the southwestern CAOB was achieved by northward subduction of the South Tianshan Ocean and subsequent collision of the CTB and the Karakum-Tarim cratons at~320 Ma. Notably, recent studies suggest that a trench-arc-back-arc basin system developed in the northern Karakum during Carboniferous times Worthington et al, 2017), which differs from the here suggested tectonic evolution that favors a transition of the northern Tarim Craton from a trench-arc-back-arc system to a passive margin at~390-380 Ma.…”
Section: 1029/2018jb015689contrasting
confidence: 94%
“…No significant exposures of magmatic rocks younger than ca. 250 Ma exist in the westernmost Tian Shan (Käßner et al, ; Worthington et al, ). Older, Paleozoic zircon U–Pb age populations could have been derived from either the Tian Shan or the Pamir Mountains.…”
Section: Discussionmentioning
confidence: 99%
“…Basement in the Tajik Basin consists of Proterozoic to Paleozoic continental crust that was accreted onto Asia during the late Carboniferous to early Permian (Burtman & Molnar, ; Schwab et al, ). Carboniferous to Permian igneous and metamorphic rocks associated with this subduction–accretion event are widely exposed in the westernmost Tian Shan Worthington et al, ) (Figure b). Permian and Triassic sedimentary rocks are locally present on the Tajik Basin margins and are thought to be locally present at depth (Nikolaev, ) (Figure b).…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…2). In the MTS and NTS, Pennsylvanian -Early Permian ages are mainly reported from the Chatkal-Kurama mountain ranges and Hercynian granitoids also occur to a minor extent in mountain ranges adjacent to the Naryn and Issyk-Kul basins (Alekseev et al, 2009;Glorie et al, 2010;De Grave et al, 2011;Seltmann et al, 2011;Macaulay et al, 2016 and references therein;Konopelko et al, 2017b;Worthington et al, 2017) (Fig. 2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%